Performing National Identity - the Case of Pavao Ritter Vitezović (1652-1713) - Blažević, Zrinka (Array, 2003)
The historiographical writings of the Croatian Baroque polymath Pavao Ritter Vitezović (1652-1713), have been included in the canon of "basic works of Croatian national politics" by the traditional "national" historiography. The question therefore arises which symbolic models, ideological concepts and narrative constructions of his discourse seemed to be "state-making" and "nation-making" within its interpretative framework. I shall try to show how Vitezović's performative historiographical discourse produces such an effect, and demonstrate how this discourse creates and makes legitimate the symbolic construction of national identity, creating a virtual, utopian artefact -a "revived Croatia." However, even though mechanisms, strategies and devices accounting for its internal cohesion and persuasiveness can be identified in the dominant semantic layer of this performative discourse, it at the same time lends itself to an analysis exposing its "burried grammar" of internal contradictions, mostly contextually determined, destabilising and disintegrating it. This of necessity makes the "national" reading reductive, proposing instead canonical texts as polyphonic cultural artefacts bearing imprints of various discoursive and contextual reinscriptions.